Characterization of ES10 lytic bacteriophage isolated from hospital waste against multidrug-resistant uropathogenic E. coli - Nawaz, Aneela; Zafar, Sabeena; Alessa, Abdulrahman H.; Khalid, Nauman Ahmed; Shahzadi, Muqaddas; Majid, Alina; Badshah, Malik; Shah, Aamer Ali; Khan, Samiullah (Frontiers in Microbiology, 2024)
Escherichia coli is the major causative agent of urinary tract infections worldwide and the emergence of multi-drug resistant determinants among clinical isolates necessitates the development of novel therapeutic agents. Lytic bacteriophages efficiently kill specific bacteria and seems promising approach in controlling infections caused by multi-drug resistant pathogens. This study aimed the isolation and detailed characterization of lytic bacteriophage designated as ES10 capable of lysing multidrug-resistant uropathogenic E. coli. ES10 had icosahedral head and non-contractile tail and genome size was 48 315 base pairs long encoding 74 proteins. Antibiotics resistance, virulence and lysogenic cycle associated genes were not found in ES10 phage genome. Morphological and whole genome analysis of ES10 phage showed that ES10 is the member of Drexlerviridae. Latent time of ES10 was 30 minutes, burst size was 90, and optimal multiplicity of infection was 1. ES10 was stable in human blood and subsequently caused 99.34% reduction of host bacteria. Calcium chloride shortened the adsorption time and latency period of ES10 and significantly inhibited biofilm formation of host bacteria. ES10 caused 99.84% reduction of host bacteria from contaminated fomites. ES10 phage possesses potential to be utilized in standard phage therapy.